PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE REHEARSAL PAIRS DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 14 PADANG - Suri, Mayang Intan; Aima, Zulfitri; Mardiyah, Ainil (STKIP PGRI Sumbar, 2013)
This research is motivated by the studentâs understanding of mathematical concepts are still low and cooperation among students who are less intertwined. This reseacrh is aimed at knowing the studentâs mathematical concept by applying the active strategy learning with practice â rehearsal pairs type accompanied with LKS better than the understanding of studentâs mathematical concept by applying conventional learning. The type of this reserach is experimental that used random design on the subject. Population of this research is the studentâs of XI IPA2 which consist of four classes. This research used random sampling, XI IPA2 as experimental class, and XI IPA1 as control class. Instrument of this research is final test of studentâs understanding mathematical concept in the form of essay with the reliability test is 0,853, meaning given problem reliably. Based on the analysis of the data is known that both of the class sampleÂ distribute normally and homogeneous on the real level Â Â hypothesis test results obtained P-value = 0,003 less than Â so, the hypothesis in this study received. Thus, it can be concluded the studentâs understanding mathematical concept by applying the active strategy learning with practice â rehearsal pairs type accompanied with LKS better than the understanding of studentâs mathematical concept by applying conventional learning.